Novel simple templates for reproducible positioning of skin applicators in brachytherapy - Villalba, Silvia Rodríguez; Perez-Calatayud, Maria Jose; Bautista, Juan Antonio; Carmona, Vicente; Celada, Francisco; Tormo, Alejandro; García-Martinez, Teresa; Richart, José; Ortega, Manuel Santos; Silla, Magda; Ballester, Facundo; Perez-Calatayud, Jose (Journal of Contemporary Brachytherapy, 2016)
Purpose : Esteya and Valencia surface applicators are designed to treat skin tumors using brachytherapy. In clinical practice, in order to avoid errors that may affect the treatment outcome, there are two issues that need to be carefully addressed. First, the selected applicator for the treatment should provide adequate margin for the target, and second, the applicator has to be precisely positioned before each treatment fraction. In this work, we describe the development and use of a new acrylic templates named Template La Fe-ITIC. They have been designed specifically to help the clinical user in the selection of the correct applicator, and to assist the medical staff in reproducing the positioning of the applicator. These templates are freely available upon request. Material and methods: Templates that were developed by University and Polytechnic Hospital La Fe (La Fe) and Hospital Clínica Benidorm (ITIC) in cooperation with Elekta, consist of a thin sheet made of transparent acrylic. For each applicator, a crosshair and two different circles are drawn on these templates: the inner one corresponds to the useful beam, while the outer one represents the external perimeter of the applicator. The outer circle contains slits that facilitate to draw a circle on the skin of the patient for exact positioning of the applicator. In addition, there are two perpendicular rulers to define the adequate margin. For each applicator size, a specific template was developed. Results: The templates have been used successfully in our institutions for more than 50 patients’ brachytherapy treatments. They are currently being used for Esteya and Valencia applicators. Conclusions : The template La Fe-ITIC is simple and practical. It improves both the set-up time and reproducibility. It helps to establish the adequate margins, an essential point in the clinical outcome.